Association between medication adherence and illness perceptions in atrial fibrillation patients treated with direct oral anticoagulants: An observational cross-sectional pilot study. - Motoyasu Miyazaki; Akio Nakashima; Yoshihiko Nakamura; Yuya Sakamoto; Koichi Matsuo; Miwa Goto; Masanobu Uchiyama; Keisuke Okamura; Ryoko Mitsutake; Hidenori Urata; Hidetoshi Kamimura; Osamu Imakyure (PLoS ONE)
Objective The aim of this study was to examine the association between medication adherence and illness perceptions, and to explore the factors associated with poor medication adherence in atrial fibrillation (AF) patients receiving direct oral anticoagulants (DOACs) in a real-world clinical setting. Methods An observational cross-sectional pilot study was conducted at a single Japanese university hospital. One hundred and twenty-nine patients who were diagnosed with AF and who were taking DOACs were recruited from outpatients between January 4th and April 25th, 2017. We evaluated medication adherence to DOACs using the Morisky Medication Adherence Scale-8 (MMAS-8) and illness perceptions using the Brief Illness Perception Questionnaire (BIPQ). The patients' characteristics and clinical data were collected from electronic medical records. Results Ninety-nine (76.7%) patients (male, n = 74; mean age, 71.4±9.8 years) participated in this study. According to the MMAS-8, 21 (21.2%) of the patients were classified into the poor adherence group (MMAS-8 score of <6), and 78 (78.8%) were classified into the good adherence group (MMAS-8 score of 6-8). A multivariate logistic regression analysis revealed that age (per year, odds ratio [OR] 0.912, 95% confidence interval [CI] 0.853-0.965, p = 0.001), a history of warfarin use (OR 0.181, 95% CI 0.033-0.764, p = 0.019), duration of DOAC exposure (per 100 days, OR 1.245, 95% CI 1.084-1.460, p = 0.001), and the BIPQ emotional response score (per 1 point, OR 1.235, 95% CI 1.015-1.527, p = 0.035) were significantly associated with poor medication adherence in AF patients receiving DOACs. Conclusion Poor medication adherence to DOACs was strongly associated with a stronger emotional response (i.e. stronger feelings of anger, anxiety, and depression), as well as younger age, the absence of a history of warfarin treatment, and longer DOAC exposure. Further evaluation of the factors associated with medication adherence in AF patients and the development and execution of strategies for improving poor adherence are warranted in the real-world clinical setting.